THE ROLE OF ATTENTION IN ESL CLASSROOM IN OPEN AND DISTANCE LEARNING SETTING - Tg Nur Liyana (Journal of Islamic, Social, Economics and Development, 2022)
The present paper reviews previous researchers’ discussions on the role of attentionin second language learning, and its significance and limitations in open and distance learning.Certainly, teachers in ESL classrooms make instructional decisions to optimally harness theirlearners’ attention. That said, to what degree does attention contribute towards learning?Secondly, how is attention influenced by open and distance ESL learning (ODL)? Thirdly, whatare the potential distractions that attenuate or divert attention in the ODL setting? Amid therecent global COVID-19 pandemic outbreak, school attendance has been restricted for moststudents worldwide and online learning has become the only available option. In Malaysia,ODL has been extensively used, especially at the higher education level, and it is expected tobe used toward the year’s end irrespective of the academic communities’ readiness.Additionally, the online learning method known as flipped classroom has been applied tocomplement ODL. In the present review, the authors sought to highlight the gap in discourseon the role (and limits) of attention during ESL learning in the ODL setting in Malaysia, andoutline the potential distractions that occur during ESL lessons in the newly pandemic-adaptedcontext.